WŁADIMIRA PROPPA DZIENNIK STAROŚCI. 1962-196… - Komisaruk, Ewa (Przegląd Rusycystyczny, 2017)
The author of the article analyses Diary of Old Age. 1962–196... by Vladimir Propp, a world-renowned Russian scholar and author of fundamental works on folklore (e.g. Morphology of the Tale, 1928; Historical Roots of the Wonder Tale, 1946). The diary was published for the first time in 1995, on the centenary of the folklorist’s birth. It covers the period from 28 March 1962 until 25 July 1970. The author of the article discusses the practice of diary writing, frequency of entries, their length as well as linguistic and stylistic features; in addition, she describes the functions of the diary and the role it played in the life of an ageing man. The author pays particular attention to the fragments directly dealing with experiencing ageing and old age. Her analysis of the diary shows that for Propp old age was not a time dominated by apathy, weariness and acute loneliness. It was an element of the world order, a time of intellectual activity, a period of continuous self-improvement.